Velocity and Density Cross Sections of the Upper Part of the Lithosphere within the North Urals Segment - Martyshko, P. S.; Tsidaev, A. G.; Kolmogorova, V. V.; Ladovskii, I. V.; Byzov, D. D. (Izvestiya. Physics of the solid earth, 2022)
—The seismic data acquired by the Bazhenov Geophysical Expedition on the regional DSS profiles are revised to study the structure of the Earth’s crust in the northern part of the Ural region. Seismic material is reprocessed by two-dimensional (2D) seismic tomography inversion, and sections of crustal velocity gradient constructed in the format of grid functions for five profiles located within the studied trapezoidal area with geographical coordinates 58° N, 64° N, 54° E, 72° E. In the same format, density sections are constructed. The coefficients of empirical correlation “density–velocity” are calculated using the solution algorithm of 2D inverse gravimetric problem.